Pelvic inflammatory disease: Pathophysiology - Gutiérrez Ramos, Miguel (2015)
Man reproduces sexually, by sexual intercourse, and there is the possibility to transmit a series of diseases by this route. Pelvic inflammatory disease (PID) involves upper reproductive tract inflammatory disorders. We review in this article PID pathogenesis, immunologic factors, immunity against bacteriae, adaptation mechanisms, all these concepts necessary for treatment based on knowledge of PID causative agents and host response.